Factors Enhancing Member Commitment to Trade Unions in the Hospitality Industry in Zimbabwe - Farai Ncube (Sciedu Press, 2023)
Trade unions in the hospitality industry have long served an important and vital role, acting as the vanguard to protect the worker’s rights and their financial livelihood, hence stressing their importance. Their future however remains hanging in balance as they continue to face an array of challenges and changes threatening their existence. In this paper the researcher attempt to respond to the question on, ‘why would individuals choose to be loyal and committed to trade unions?’ Finding through a 5 point likert scale administered on 227 members belonging to the Zimbabwe Catering and Hotel workers Union (ZCHWU) and interviews conducted with 18 union officials reveals that commitment is determined by the ability of the union to satisfy member expectations. Findings reveals that member commitment manifest itself through individual’s strong desire to remain a member of the union; willingness to exert high effort on behalf of the union as well as belief in the union goals and leadership. The study concludes that the unions’ ability to satisfy and meet its member’s expectation contributes to trade union commitment.